Genetic Diversity and Relationships Among Tunisian Wild and Cultivated Rosa L. Species - Khouloud Chtourou; Juan Alfonso Salazar; Germán Ortuño-Hernández; Najla Mezghani; Neila Trifi-Farah; Pedro Martínez-Gómez; Lamia Krichen (Plants)
Assessing and determining genetic diversity in rose species is a crucial step for conservation efforts, the establishment of a core collection, and the development of new varieties. This study represents the first investigation of genetic diversity among various rose species at different ploidy levels in Tunisia, with the aim of elucidating the genetic structure of the Rosa genus. It encompasses both spontaneous and cultivated accessions, featuring local and introduced species recognized for their adaptability, ornamental value, and fragrance. A total of 114 accessions representing eight rose species were collected. Significant genetic diversity was assessed using seven SSR markers, yielding an average of 21 alleles per locus and a PIC value ranging from 0.882 to 0.941. The results identified 343 phenotypic alleles across the seven primers, with 72 for the primer RhE2b (LG6), 55 for H10D03 (LG7), and 54 for RhB303 (LG2). One key finding was that most perfumed rose accessions (R. damascena Mill. and R. centifolia L.) are distinct from the other rose accessions, indicating a unique genetic pool for these roses. Another important finding was that the Tunisian accessions of ‘Rose of Ariana’ were closely related to R. centifolia accessions, commonly known as the ‘Rose of May’ from Grasse, France. To clarify the phylogeny of this species or subspecies, further molecular studies are warranted. Additionally, nomenclature confusion was identified between R. sempervirens L. and R. canina L. in the northwestern region of Tunisia, indicating that all wild accessions correspond to R. sempervirens.